The Effect of Humic Acid and Micro Compound Fertilizer on Soil Microorganism Population and Upland Rice Yield in Coastal Land - Nova Angelina Sibagariang; Yudhi Harini Bertham; Heru Widiyono; Anandyawati; Kartika Utami (Department of Soil Science, Faculty of Agriculture, University of Bengkulu, 2022)
This study aims to determine the effect of humic acid and micro compound fertilizer on soil microbial populations and yields of Inpago10 varieties of upland rice in coastal areas. This research was conducted from August to December 2021 in Beringin Jaya village, Muara Bangkahulu District, and analysis of soil and plant samples at the Soil Science Laboratory, Faculty of Agriculture, University of Bengkulu. This study was prepared using a randomized complete block design (RCBD) with 2 factors.The first factor is the dose of humic acid which consists of 3 levels, namely 0 L ha-1 , 8 L ha-1, and 16 L ha-1. The second factor is a compound micro fertilizer consisting of 2 levels, namely 0 g ha-1 and 70 g ha-1. Each treatment was repeated 4 times, resulting in 24 experimental units. Observation variables include C-organic (%), respiration, total microbial population, pH KCl, pH H2O, plant height (cm), the number of grains per panicle, plant dry weight (g), root dry weight (g), and weight per plot (g plot-1). The Data were analyzed using variance analysis and extended with DMRT at the level of 5%. The results showed that the application of humic acid was able to stimulate the population of soil microorganisms by 38.91% and the addition of micro compound fertilizer was able to increase the yield of weight per plot by 26.69%.